2004
DOI: 10.1128/jcm.42.12.5925-5927.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recovery ofCandidaSpecies from Subgingival Sites in Human Immunodeficiency Virus-Positive and Healthy Children from Rio de Janeiro, Brazil

Abstract: The prevalence of subgingival Candida species was studied in 52 human immunodeficiency virus (HIV)-positive and 42 HIV-negative children. Candida was cultured from 22 (42.3%) and 3 (7.1%) HIV-infected and control children, respectively. C. albicans was the most common Candida species isolated from HIV-infected children, followed by C. dubliniensis, C. glabrata, and C. tropicalis. In the HIV-positive group, the prevalence of Candida isolation was significantly higher in children who presented with low CD4+-T-ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 19 publications
2
63
1
1
Order By: Relevance
“…Oral candidiasis presents not a single clinical entity, but instead a spectrum of very different clinical variants (e.g. pseudomembranous candidiasis, erythematous candidiasis, denture stomatitis and angular cheilitis) [32][33][34]. Oropharyngeal candidiasis is the most common opportunistic fungal infection in patients infected with human immunodeficiency virus (HIV), occurring in as many as 90% patients at some point during the course of HIV disease [34][35][36].…”
mentioning
confidence: 99%
“…Oral candidiasis presents not a single clinical entity, but instead a spectrum of very different clinical variants (e.g. pseudomembranous candidiasis, erythematous candidiasis, denture stomatitis and angular cheilitis) [32][33][34]. Oropharyngeal candidiasis is the most common opportunistic fungal infection in patients infected with human immunodeficiency virus (HIV), occurring in as many as 90% patients at some point during the course of HIV disease [34][35][36].…”
mentioning
confidence: 99%
“…However the use of www.intechopen.com highly active antiretroviral therapy (HAART) was associated with decreases in the prevalence of oral diseases. In a study comparing the oral microbiology of HIV-positive children with that of controls, the prevalence of gingivitis was significantly higher in the HIV-positive group (89.4%) than in the healthy group (40.5%) (Portela et al, 2004). It was also found that the frequency of yeast isolation correlated positively with the severity of the gingival condition in the HIVinfected group, because 95% of infants who presented with Candida had inflammation of the gingivae.…”
Section: Hiv-associated Gingivitismentioning
confidence: 70%
“…Portela et al in a series of studies on LGE demonstrated the possibility of Candida as the aetiological agent of LGE in HIV-infected patients. Subgingival plaque samples of HIV-infected children contained 42.3 % Candida species compared to 7.1 % HIV-negative children (Portela et al 2004 ). C. albicans was the most commonly recovered species, but other non-albicans species such as Candida dubliniensis , Candida glabrata and Candida tropicalis and mixed species were also present in the subgingival plaque samples.…”
Section: Microbiology Of Linear Gingival Erythemamentioning
confidence: 94%